Występowanie jodły pospolitej (Abies alba Mill.) w południowo-wschodniej części Puszczy Iłżeckiej - Bis, Ryszard; Dobrowolska, Dorota (Leśne Prace Badawcze, 2012)
The study was conducted in Starachowice Forest District in Iłżecka Forest in southern part of Poland. Silver fir was the main tree species in Iłżecka Forests in the past. Nowadays the area is occupied by Scots pine forests, however the percentage of silver fir has recently increased again. The distribution of silver fir is uneven in this region. The article tries to answer the following questions: What does determine the distribution of silver fir stands in Iłżecka Forest? Do the geological conditions influence the occurrence of fir stands? The distribution of fir stands was investigated according to the main environmental parameters such as site types, soil types and underlying geology. The data on stand description were collected from management plans (period 1941–2005), general maps of the Starachowice Forest District and the Geological Map of Poland. The distribution of fir stands depended on forest site types. Soil type did not influence the occurrence of silver fir stands. Forests with silver fir were found both on Mesozoic rock from the Middle Jurassic period and on the strip next to the border separating Middle and the Upper Jurassic periods. More homogeneous fir areas were present on the geological bedrock from the Tertiary and the Middle Jurassic period rather than the Upper Jurassic, which may indicate that geological base substantially influenced fir expansion in the research area.